Muscle mass and association to quality of life in non‐small cell lung cancer patients. Issue 5 (10th May 2017) - Bye, Asta; Sjøblom, Bjørg; Wentzel‐Larsen, Tore; Grønberg, Bjørn H.; Baracos, Vickie E.; Hjermstad, Marianne J.; Aass, Nina; Bremnes, Roy M.; Fløtten, Øystein; Jordhøy, Marit
Abstract: Background: Cancer wasting is characterized by muscle loss and may contribute to fatigue and poor quality of life (QoL). Our aim was to investigate associations between skeletal muscle index (SMI) and skeletal muscle radiodensity (SMD) and selected QoL outcomes in advanced non‐small cell lung cancer (NSCLC) at diagnosis. Methods: Baseline data from patients with stage IIIB/IV NSCLC and performance status 0–2 enrolled in three randomized trials of first‐line chemotherapy ( n  = 1305) were analysed. Associations between SMI (cm 2 /m 2 ) and SMD (Hounsfield units) based on computed tomography‐images at the third lumbar level and self‐reported physical function (PF), role function (RF), global QoL, fatigue, and dyspnoea were investigated by linear regression using flexible non‐linear modelling. Results: Complete data were available for 734 patients, mean age 65 years. Mean SMI was 47.7 cm 2 /m 2 in men ( n  = 420) and 39.6 cm 2 /m 2 in women ( n  = 314). Low SMI values were non‐linearly associated with low PF and RF (men P  = 0.016/0.020, women P  = 0.004/0.012) and with low global QoL ( P  = 0.001) in men. Low SMI was significantly associated with high fatigue ( P  = 0.002) and more pain ( P  = 0.015), in both genders, but not with dyspnoea. All regression analyses showed poorer physical outcomes below an SMI breakpoint of about 42–45 cm 2 /m 2 for men and 37–40 cm 2 /m 2 for women. In both genders, poor PF and more dyspnoea were significantly associated with low SMD. Conclusions: Low muscle mass in NSCLC negatively affects the patients' PF, RF, and global QoL, possibly more so in men than in women. However, muscle mass must be below a threshold value before this effect can be detected.